2005
DOI: 10.1258/1357633054461688
|View full text |Cite
|
Sign up to set email alerts
|

Effect of home-based telecardiology on chronic heart failure: Costs and outcomes

Abstract: Chronic heart failure (CHF) remains a common cause of disability. We have investigated the use of home-based telecardiology (HBT) in CHF patients. Four hundred and twenty-six patients were enrolled in the study: 230 in the HBT group and 196 in the usual-care group. HBT consisted of trans-telephonic follow-up and electrocardiogram (ECG) monitoring, followed by visits from the paramedical and medical team. A one-lead ECG recording was transmitted to a receiving station, where a nurse was available for reporting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(73 citation statements)
references
References 8 publications
3
70
0
Order By: Relevance
“…[6][7][8][9][10][11][12][13][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56] Twenty-one studies applied to general populations, largely older adults and together included 10 445 patients. 1,[57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74] Four studies applied to unique populations.…”
Section: Population and Contextmentioning
confidence: 99%
“…[6][7][8][9][10][11][12][13][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56] Twenty-one studies applied to general populations, largely older adults and together included 10 445 patients. 1,[57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74] Four studies applied to unique populations.…”
Section: Population and Contextmentioning
confidence: 99%
“…Thus, it is mandatory to build a a completely new standard of assistance, involving a strict cooperation and information exchange among heart failure specialists, dedicated nurses and general practitioners: indeed, a patient should be followed, according to his/her clinical status, by anyone of these caregivers in different times [39]. A network of telenursing for patients with hert failure could help the General Practioner, allowing his/her regular exchange of clinical information and consulting with the Heart Failure Center [25,26]: an experience of this kind is currently ongoing in many Italian regions, and among them is Lombardia. We have already suggested that a Telemonitoring similar to the ICAROS model could take place in a first phase, soon after hospital discharge when patients are more fragile [27].…”
Section: Icaros and Other Telemonitoring/telecare Modelsmentioning
confidence: 99%
“…After TEMISTOCLE, a network for the integrated management of patients with chronic, stable heart failure has been developed in Italy, with favorable preliminary results [23][24][25][26]. To fill the gap between these models of home-based care for stable patients, and the hospital-based care for acute and sicker patients, we designed the ICAROS project (Integrated care vs Conventional intervention in cArdiac failure patients: Randomized Open label Study), in which the clinical approach of heart failure specialists was integrated with Internet and wireless technologies with the aim of developing a decision-making model that could fit the needs of fragile patients [27].…”
Section: Introductionmentioning
confidence: 99%
“…However, the platform used was not integrated into the patients EHR system. A clear outcome effects of a home-based tele-cardiology service has been verified by Scalvini et al (2005), where the patients' ECG recordings automatically were transmitted to a receiving station available for trained nurses (telemonitoring), also this solution was a stand-alone receiving database. In a report on remote monitoring, the U.S. Department of Health and Human Services has described use cases to define possible solutions for information exchange and integration of patient-monitored data into a national health information technology (U.S. Dept of Health and Human Services (2008).…”
Section: Integration Of Remote Monitoringmentioning
confidence: 93%